Implementasi Project-Based Learning (PjBL) dalam LMS E-Learning Hamzanwadi untuk Meningkatkan Kedisiplinan dan Dokumentasi Portofolio Mahasiswa pada Mata Kuliah Ekonometrik - Farhana Muhammad; Huzain Jailani; Isfi Sholihah; Putri Ayu Anisatus Shalikha; Deliyana Wika Kinanti; Ewit Nurdayanti (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to evaluate the effectiveness of Project-Based Learning (PjBL) implementation within the Hamzanwadi E-Learning Learning Management System (LMS) in improving students' learning discipline and digital portfolio documentation in the Econometrics course. The study employed a mixed methods approach. The subjects were 159 fifth-semester students of the Economics Education Study Program at Hamzanwadi University in the 2025/2026 Academic Year. Quantitative data were obtained through analysis of LMS activity logs, quiz participation, and project assignment submissions, while qualitative data were collected through interviews, focus group discussions, and analysis of students' academic portfolios. Data analysis was conducted descriptively and inferentially to measure the level of discipline, learning engagement, and portfolio documentation quality. The results showed that across seven lecture topics, student participation in quizzes reached an average of 97.9%, while participation in project assignment submissions averaged 74.3%. These findings indicate that the implementation of LMS-based PjBL can improve students' discipline, learning regularity, and academic responsibility. Furthermore, the LMS effectively functions as a systematic and structured digital portfolio documentation medium. Thus, the integration of PjBL into Hamzanwadi's E-Learning LMS has been shown to contribute positively to strengthening students' learning discipline and managing their academic portfolios in Econometrics.